The Backbone of Key Successful Branding Strategies in the 21st Century: Innovation in Design Technology, Decision Making on Product Quality, and Collaborative Communications - Ho, Cheong Lee; Noraziah, Ahmad; Herawan, Tutut (Information Science Reference, 2017)
hi the 21st century, the awareness of applying recent advanced intelligent technologies to promote a firm 's brand image ir the key to the success of expanding its business. Sttch implication demands efforts in strategic planning and massive investment from the. top management team, However, most researches on branding Strategies are narrowed to advertisement or classical marketing. Insufficient research on the backbone of making key successful branding strategies to effectively apply the intelligent terhnologies hinders the development of branding strategies. This chapter identifies three aspects: innovation in design technology, decision making on product quality, and coltutioraitve communications to be the critical elements of the backbone. The methodology utilizes the power of the advanced computational technologies to generate innovative designs in a collnharative communication frame-nark. Decision making on the quality of designs is monitored with EG-Kano reference models. Four case Studies demonstrate that the backbone has potentials leading to ever-greater economic benefits.